Research on the Excavation CXXIV in the South-Eastern Part of the Bolgar Fortified Settlement - Volkov Igor V.; Lopan Oxana V.; Sitdikov Airat G. (Поволжская археология, 2023)
The article presents the results of studies carried out in the south-eastern part of the Bolgar fortified settlement in 2013. The Golden Horde objects belonging to different periods have been identified here. Since early coins make up more than 10% of the numismatic collection, this suggests that the site began to be developed already in the 2nd half of the 13th century. The pits in the southwest corner of the excavation can be attributed to this time. Unique are the finds of two dinars of the 12th century and the middle of the 13th century, belonging to the initial stage of the development of the area. А wooden house (structure No. 2) with a kang was built on the site within the period from the 2nd half of the 13th century to the 1230ies. Probably, the construction of three pits with large poles is related to the time of the wooden house, as well as, perhaps, a stockade. The building was destroyed by a fire. The next construction period is associated with a stone building (structure No. 1), soon erected on the place of the burned house. According to the coins found here, the stone building with a kang was built here no earlier than in the 1340s and functioned until the 1360s. The horizon of the building of a stone house is marked by layers of construction debris that filled the most of the pits on the excavation. The stone masonry of the building was almost completely taken and used as building materials, most likely already at the beginning of the 20th century, but the well-preserved contours of the foundation trenches, densely filled with lime and stone fragments, allow us to restore the layout of the building. The portal of the building, located on the north side, was decorated with two pylons, that were the base of the arched entrance, and a square construction, probably a turret, sided with the western one. The uniqueness of the building consists in an amazing combination of features of private residential and public architecture. After the 1360s, the site became desolate, and this wasteland was used as a cemetery: near the remains of a stone building the burials with fragments of its architectural details in the filling were found. The studied estate was related geographically with the quarter of the "Mongolian administration" at the Small Minaret, where dwellings with kangs were concentrated.